Profile of Enviromental Literacy of Students on the Topic of Renewable Energy - Suratmi Suratmi; Laihat Laihat; Marwan Pulungan; Aswasulasikin Aswasulasikin; Nadiah Tri Rahma; Latisya Ardi Utami (Jurnal Penelitian Pendidikan IPA, 2025)
Environmental issues are becoming increasingly urgent, particularly concerning the transition to environmentally friendly renewable energy. This study aims to map the environmental literacy profile of grade VI elementary school students in the context of renewable energy, covering knowledge, attitudes, environmental utilization, and interest in environmental issues. This descriptive qualitative study utilized an instrument adapted from The Scale of Environmental Literacy (SEL). The instrument comprises four main components: (1) knowledge, (2) attitudes, (3) environmental utilization, and (4) interest in environmental issues, each measured using a Likert scale with 10 statements. The instrument was validated by experts and tested on 10 students before being distributed to 91 grade VI students from several elementary schools in Palembang via Google Forms. The findings indicate that students have a good basic understanding of environmental concepts but face challenges in comprehending renewable energy in depth. Students' positive attitudes toward the environment were relatively high, though their awareness of plastic-related issues remains low, indicating the need for increased consciousness. Their environmentally friendly behaviors were generally consistent, albeit with some inconsistencies. Students showed a high interest in environmental issues but require reinforcement through real-world contextual learning approaches and active support from teachers and parents. These findings can serve as a basis for designing more effective and contextual learning strategies in environmental education at the elementary level